Virtual Avatar for Emotion Recognition in Patients with Schizophrenia: A Pilot Study - Marcos-Pablos, Samuel; González-Pablos, Emilio; Martín-Lorenzo, Carlos; Flores, Luis A.; Gómez-García-Bermejo, Jaime; Zalama, Eduardo (Frontiers in Human Neuroscience, 2016)
Persons who suffer from schizophrenia have difficulties in recognizing emotions in others’ facial expressions, which affects their capabilities for social interaction and hinders their social integration. Photographic images have traditionally been used to explore emotion recognition impairments in schizophrenia patients, but they lack of the dynamism that is inherent to facial expressiveness. In order to overcome those inconveniences, over the last years different authors have proposed the use of virtual avatars. In this work, we present the results of a pilot study that explored the possibilities of using a realistic-looking avatar for the assessment of emotion recognition deficits in patients who suffer from schizophrenia. In the study, 20 subjects with schizophrenia of long evolution and 20 control subjects were invited to recognize a set of facial expressions of emotions showed by both the said virtual avatar and static images. Our results show that schizophrenic patients exhibit recognition deficits in emotion recognition from facial expressions regardless the type of stimuli (avatar or images), and that those deficits are related with the psychopathology. Finally, some improvements in recognition rates (RRs) for the patient group when using the avatar were observed for sadness or surprise expressions, and they even outperform the control group in the recognition of the happiness expression. This leads to conclude that, apart from the dynamism of the shown expression, the RRs for schizophrenia patients when employing animated avatars may depend on other factors which need to be further explored.